Women's Activist Organizing in US History : A University of Illinois Press Anthology - Durante, Dawn (Book collections on Project MUSE., 2022)
"This volume commemorates the 35th anniversary of the Women, Gender, and Sexuality in American History series in 2022. The anthology brings together chapters and excerpts from previously published books in the series that reflect the breadth of the intellectual commitments of the Women, Gender, and Sexuality in American History series--including material from one of the first books in the series, many of its most popular chapters and award-winning books, and its most recent bestseller. Curated around the theme of organizing over two hundred years, each piece in the anthology shows a different dimension of nineteenth and twentieth century labor, activist, legal, political, or community organizing at work within the history of women, gender, and sexuality in the United States. With an original introduction by Deborah Gray White, this compilation shows the historical and strategic breadth of the ways that women and feminists organize, reform, and resist against systems of racism, misogyny, white supremacy, and inequality"--